Numerical study of flow and mixing characteristics in a T-junction under inflow pulsation. (February 2019) - Lin, Mei; Su, Bo; Li, Shicong; Wang, Qiuwang
Abstract: In order to investigate the effect of ocean condition on flow and mixing characteristics in a horizontal T-junction pipe, a numerical analysis is conducted under inflow sinusoidal pulsation. In this study, the wall jet is focused on the velocity and temperature field. The results show that the velocity near center of the main pipe indicates sinusoidal distribution against the time, where the temperature has a strong mixing due to the inflow pulsation. Furthermore, the peak of temperature fluctuation intensity is located at the axial position of z /D=0.5. This phenomenon of wall jet under inflow pulsation is like that of impinging jet described by Kamide et al. (2009).